How policy advocacy promotes regulated antibiotic use: Evidence from meat duck farmers of China - Jinpeng Dong; Lina Wang; Lingzhi Liu; Yuanyuan Zhang; Qiang Wu; Jiajia Zhao (One Health)
Antibiotic residues resulting from the misuse of veterinary antibiotics pose a serious threat to global food safety and the ecological environment. Regulating the use of antibiotics is currently a major concern; however, existing literature on this issue remains insufficient. Therefore, to advance research in this area, this study utilizes data from 988 questionnaires collected across 9 provinces in China and employs the 3SLS systematic estimation method. It constructs an analytical framework to explore the mechanisms through which policy advocacy (PA) influences regulating antibiotics use (RAU) among meat duck farmers. Specifically, the study examines two pathways: “ PA - public opinion pressure perception (POPP) - RAU” and “ PA - moral responsibility (MR) - RAU.” Additionally, it explores the potential mechanisms through which PA impacts RAU among farmers. The results show that PA (Coef = 0.070, SE = 0.014) can promote RAU by increasing the level of POPP (Coef = 0.173, SE = 0.091). PA (Coef = 0.351, SE = 0.028) can also promote RAU by enhancing MR (Coef = 0.239, SE = 0.035). Meanwhile, this study introduces Internet use (IU) and reputational incentives (RI) as moderating variables to analyze their role in moderating the impact of PA on RAU. It was demonstrated that IU (Coef = 0.088, SE = 0.016) significantly enhances farmers' awareness of the value of RAU and amplifies the impact of PA on MR. However, IU (Coef = −0.017, SE = 0.008) was found to inhibit the effect of PA on POPP. RI fully satisfies farmers' need for “ honor “ and enhances the effectiveness of PA in promoting both POPP (Coef = 0.009, SE = 0.002) and MR (Coef = 0.058, SE = 0.004). Finally, the study proposes that the government expand PA channels, innovate methods, and combine online outreach with demonstrations to improve farmers' awareness of antibiotic use and address their reputational needs.